Insights on the combustion mechanism of ethanol and n-hexane in honeycomb monolithic type catalysts: Influence of the amount and nature of Mn-Cu mixed oxide - Morales, Maria Roxana (2017)
Mn-Cu mixed oxides were deposited by ultrasonic impregnation on ceramic honeycomb monoliths. Its catalytic performance was evaluated in the combustion of ethanol and n-hexane, VOC molecules of different chemical nature. The catalysts were characterized by N2 physisorption, SEM-EDS, XRD, X-ray fluorescence, XPS, TPR, TPD-O2 and OSC measurements. It was observed that the catalyst with the lowest content of Mn-Cu phase was the most active in the combustion of ethanol. This was attributed to the higher content of Mn4+ and the increase of lattice oxygen mobility, which would favor a Mars-van Krevelen type mechanism. The catalyst with a medium content of Mn-Cu, proved to be the most active in the combustion of n-hexane. This was associated with a high content of oxygen vacancies and easy availability of oxygen adsorbed on the surface, promoting the combustion of n-hexane, possibly through a Rideal-Eley type mechanism. The catalyst with the highest content of the Mn-Cu phase showed low activity in combustion of ethanol and n-hexane, which was attributed to a higher crystallinity of the Mn-Cu phases generated.